THE USE OF THE SUBJUNCTIVE IN THE NOVEL CHRONICLE OF A DEATH FORETOLD- ANALYTICAL STUDY - Mustafa Mohammed Rashid (American Journals Publishing, 2025)
This research analyzes the use of the subjunctive mood in Gabriel García Márquez's novel "Chronicle of a Death Foretold" from a semantic and rhetorical perspective. It examines how this mood contributes to creating atmospheres of doubt, subjectivity, and inevitability, reflecting the emotional and moral complexity of the characters. Through the analysis of representative passages from the novel, multiple linguistic functions are identified, such as the expression of desire, doubt, supposition, judgment, and unreality. This work draws on linguistic and literary sources and aims to make a valuable contribution to both discourse analysis and the teaching of Spanish as a foreign language.
Keywords: Subjunctive, translation, analisis.